Statistical Theory for Three-Point Distribution Functions of Certain Variables in Mhd Turbulent Flow in Existence of Coriolis Force in a First Order Reaction (Global Journal of Science Frontier Research, 2015)
In this paper, the three-point distribution functions for simultaneous velocity, magnetic, temperature and concentration fields in MHD turbulent flow in presence of coriolis force under going a first order reaction have been studied. The various properties of constructed distribution functions have been discussed. From beginning to end of the study, the transport equation for three-point distribution function under going a first order reaction has been obtained. The resulting equation is compared with the first equation of BBGKY hierarchy of equations and the closure difficulty is to be removed as in the case of ordinary turbulence.
Keywords: coriolis force; magnetic temperature; concentration; three-point distribution functions; MHD turbulent flow; first order reactant